Not at Your Service. Manifestos for Design - Matter, Hansuli (Birkhäuser - an imprint of De Gruyter, 2021)
Not at Your Service: Manifestos for Design brings together the broad spectrum of beliefs, subjects and practices of designers at Zurich University of the Arts. It offers different approaches and insights on the present-day role and impact of design. It is not conceived as a finished project, but as a fluid document of its time. Collaborative design, interaction within complex systems, attention economics, the ecological shift, visual literacy, gender-neutral design, quick and dirty design ethnography, social responsibility, the value of ugliness, death futures, immersive technologies, identity and crises, design as a transformative discipline - all of these topics are presented for debate with passion, conviction and professional expertise.